IMPLEMENTASI MEDIA DIORAMA PADA PEMBELAJARAN IPAS KELAS III DI SDN LAYUNGSARI 2 - Elita Fitriyani; Sandi Budiana; Hani Nur’Azizah (STKIP Subang, 2024)
This study aimed to investigate the implementation of diorama media in science learning for third-grade students at SDN Layungsari 2. The research problem was the lack of effective learning media to enhance students' understanding of science concepts. This study employed a qualitative approach with a case study design. Data were collected through observations, interviews, and document analysis. The results showed that the use of diorama media significantly improved students' active participation, motivation, and understanding of science concepts. Students were more engaged in the learning process and able to construct their own knowledge through hands-on activities with the diorama. However, there were some challenges faced by the teacher in preparing the diorama and managing the learning process. This study recommends that diorama media can be a valuable tool to enhance science learning, and further research is needed to explore its effectiveness in different contexts.